CUSTOMER SATISFACTION ANALYSIS ON SALES ENGINEERING SERVICE USING SERVQUAL AND FACTOR ANALYSIS IN PACKAGING INDUSTRY - Vahlepy, Rheza; Winarno, Winarno; Azizah, Fahriza Nurul; Rinaldi, Dimas Nurwinata (PATTIMURA UNIVERSITY, 2022)
To achieve client satisfaction, every company must be able to do its best. Companies must be able to provide services that meet or surpass their consumers' expectations to achieve customer satisfaction. As a result, the goal of this research is to look at client satisfaction with the Sales Engineer services that have been delivered. Reliability, responsiveness, assurance, empathy, and tangible customer satisfaction at PT XYZ are the characteristics used in this study. 150 consumers who were served by Sales Engineers provided the data for this study. To perform data processing, this research used SERVQUAL and Factor Analysis for determining customer satisfaction. Based on the findings of the data processing with SERVQUAL, it has been determined that two variables, Assurance, and Empathy, are capable of bringing consumer satisfaction. Based on the overall analysis using Factor Analysis, it can be concluded that the majority of the services provided by the Sales Engineer are able to meet the expectations of customers, particularly in terms of the most important factor in the emergence of customer satisfaction, to encourage these customers to be loyal to the company. Customers, as well as being responsible for and the ultimate action taken by sales in response to consumer complaints.